To determine Minimum Inhibitory Concentration (MIC) of Cefixime in Mahacef® Tablet 200mg and API Cefixime trihydrate compacted IP (API) (Academia Journal of Medicine, 2023)
Antibiotic resistance is rising to dangerously high levels globally. New resistance mechanisms are emerging and spreading,  thereby threatening our ability to treat common infectious diseases. In places where antibiotics can be bought for human or animal use without  a prescription, the emergence and spread of resistance is made worse. This study endeavours to determine minimum inhibitory concentration  (MIC) of Mahacef® 200mg Tablet and Cefixime Trihydrate API, both supplied by Mankind Pharma Limited. Methodology: Antibacterial  activity of Cefixime on Salmonella enterica subsp. enterica serover Typhimurium was determined by Agar Dilution Method with Mueller  Hinton Agar. Available strain of Salmonella enterica subsp. enterica serover Typhimurium (ATCC® 14028™) was used with Inoculum size  was approximately 1000 cfu / plate. Dilutions were prepared in Phosphate buffer (pH 7.0, 0.1 mol/L) for Mahacef® 200 mg Tablet and  Cefixime Trihydrate API, and used for the study. Results: Findings of this study demonstrate that both Mahacef® 200mg Tablet and Cefixime  Trihydrate API have shown excellent antibacterial activity in vitro. MICs for the drug product as well as for the drug substance (API) are found  to be 0.1 µg/mL against Salmonella enterica subsp. enterica serover Typhimurium. Conclusion: Mahacef® 200mg andCefixime Trihydrate  API clearly establish support for its antimicrobial effectiveness and therefore, support values determined MIC for the viewpoint of medical  fraternity that Cefixime is effective for management of typhoid fever.
Keywords: Minimum Inhibitory Concentration; Cefixime; Cefixime trihydrate compacted IP; Antibiotic resistance